O Gigante abatido: o longo processo de constituição da Província do Amazonas (1821-1850) - Freitas, André Luiz dos Santos (2010)
As a means to recover the political trajectory of Rio Negro at the moment its juridical status was elevated from Captaincy to Province, this work focuses on the rivalries and political clashes between local and Pará authorities around the debates on their autonomy. After the country´s independence, Rio Negro has lost its status as a province. Thus, the study sought to bring about the long process for the establishment of Amazonas Province. In addition to the core issue, the survey provided a glimpse of absence of the stresses occurring in the Amazon region and conflicts fought in the House of Representatives (Câmara dos Deputados) for the political emancipation of Rio Negro in the regional historiography, which led to the creation of the province of Amazonas. The analysis of these struggles for Rio Negro autonomy, took into account the economic and geopolitical issues faced by regional and national authorities. Overall, this study aimed at bringing out the history of the political constitution of the state of Amazonas, often viewed as expendable if compared to subjects considered as most needed in the context of a globalized world. It is understood that the political constitution of a territory does not guarantee any of its inhabitants´ access legal, economic and political benefits, which have come out of such new order. However, autonomy is the first step towards a new beginning